2020
DOI: 10.15453/2168-6408.1642
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Acute Phases of Rehabilitation Following Shoulder Arthroplasty

Abstract: Background: Shoulder arthroplasty is a common procedure, but a lack of research regarding recovery and rehabilitation limits occupational therapists from providing appropriate education and support. The purpose of this study was to explore and understand the patient's experiences in the acute recovery phase following shoulder arthroplasty.Method: Twelve participants completed three semi-structured interviews in the first 6 weeks following surgery. A basic-interpretive approach was used before coding interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Sleep disturbances have been attributed to a positional requirement, inability to sleep in the preferred position and temperature cha nges. 7 Weinberg et al showed a progressive improvement of sleep quality after TSA, which returned to normal limits at 12 months after surgery. 15 In this study, we demonstrate that sleep disturbances peak before 6 weeks and are much less thereafter, which could reflect the association of sleep disturbances with sling use and restrictions related to positioning of the arm.…”
Section: Discussionmentioning
confidence: 94%
“…Sleep disturbances have been attributed to a positional requirement, inability to sleep in the preferred position and temperature cha nges. 7 Weinberg et al showed a progressive improvement of sleep quality after TSA, which returned to normal limits at 12 months after surgery. 15 In this study, we demonstrate that sleep disturbances peak before 6 weeks and are much less thereafter, which could reflect the association of sleep disturbances with sling use and restrictions related to positioning of the arm.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, some patients in the early rehabilitation group felt more confident and had the perception that moving their shoulder was contributing to their recovery. Another qualitative study [ 44 ] exploring patients perceptions of rehabilitation after shoulder arthroplasty reported that the sling, especially when using an abduction component, was impairing their sleep. Patients reported that they were unable to sleep because of the position, itching and temperature changes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, those patients in the early group felt more confident and had the perception that moving their shoulder was contributing to their recovery. Another qualitative study (43) exploring patients perceptions of rehabilitation after shoulder arthroplasty reported that the sling, especially when using an abduction component, was impairing patients sleep. Patients reported that they were unable to sleep because of the position, itching and temperature changes.…”
Section: Discussionmentioning
confidence: 99%